Sosialisasi Penerapan E-Commerce Untuk Meningkatkan Daya Saing UMKM di Desa Karangmulya - MH Ainulyaqien; Kisanda Midisen; Sukron Mamun; Rini Setyowati; Djoko Nugroho (Jurnal Pengabdian Pelitabangsa, 2021)
Economic growth and prosperity play an important role in improving the socioeconomic welfare of the region. Micro, small and medium enterprises (MSMEs) play an important role in community economic development. However, MSMEs often face various problems such as lack of capital, lack of product innovation, distribution and e-commerce issues, and lack of official labels and distribution permits with labels on product packaging BPOM or PIRT methods used in the implementation of this activity include direct observation and monitoring as well as taking a direct approach to business actors to practice the application of product marketing through e-commerceMSME activities limit business independence and creativity and technological developments. The main purpose of using digital marketing as a marketing tool, especially for MSMEs. Although digital marketing comes as a new approach, conventional marketing is still relevant and both can help. In discussion sessions with MSME players, they understand the importance of internet-based digital marketing and the utilisation of social media and e-commerce platforms to grow their businesses. Information on target markets, digital marketing objectives, and types of digital marketing media have been delivered in a way that is easily understood by MSME players. This activity also opened up insights into the use of social media and e-commerce platforms as tools to attract attention and interact with consumers more effectively. They understand the importance of internet-based digital marketing and the use of social media and e-commerce platforms to develop their businesses. Information on target markets, digital marketing objectives, and types of digital marketing media have been delivered in a way that is easily understood by MSME players.